Advances in glycolysis research in gastric cancer: molecular mechanisms, regulatory networks, and therapeutic potential - Dong, Jungang; Li, Weiyan; Ma, Liang; Yang, Jinrong; Gan, Decheng; Xue, Haixia; Pu, Li; Zhang, Lili; Zhang, Kelan; Jia, Yonglong; Ma, Qingyu (Frontiers in Oncology, 2025)
Glycolysis is a central metabolic pathway in cancer cells, contributing significantly to the initiation, progression, and therapeutic resistance of gastric cancer. Advances in molecular biology and metabolomics have clarified the regulatory landscape of glycolysis, particularly its interactions with the tumor microenvironment and key signaling pathways. However, important gaps remain in understanding the precise functions and interactions of key regulatory factors. This review presents an overview of recent progress in glycolysis research in gastric cancer, focusing on essential regulators such as CENPU, CD73, SALL4, and MAOA, non-coding RNAs (e.g., circRNAs, lncRNAs, and miRNAs), and exosome-mediated metabolic reprogramming driven by tumor-associated macrophages. It also discusses the prognostic value of glycolysis-related genes and their potential as therapeutic targets, including the application of natural compounds and small-molecule inhibitors in anti-glycolytic strategies. These findings provide valuable insights into the metabolic mechanisms underlying gastric cancer and highlight the potential for developing metabolism-targeted therapies.